Design of A Thematic Approach as An Innovational Effort for Learning Arabic Language at Islamic Junior High School - Agung Muttaqin; Faedurrohman Faedurrohman; Lukmanul Hakim; Rizkia Syafia Qalbi; Ulya Qonita; Tyar Muhamad Khadafi; Mara Irpan Pane (Al-Muyassar: Journal of Arabic Education, 2023)
This study aims to determine the efforts to increase innovation in learning Arabic at the Mutawasitah Madrasah by using a thematic approach design. This study uses a qualitative method that makes library data as primary data. The secondary data are the results of research from various sources, especially from journals on design and education. This research has found that the design of the thematic approach is an effort to increase innovation in learning Arabic at the Muthawasitah Madrasah. The results of this study: 1) Thematic Approach in Learning. 2) Characteristics of the Thematic Approach. 3) Thematic-based Arabic learning 4). Design of a Thematic Approach in Learning Arabic. 5). Design of a Thematic Approach as an Innovation Effort in Learning Arabic. Based on these findings, it can be concluded that the process of designing a thematic approach is one of the efforts to increase Arabic learning innovation. Keywords: Thematic Approach, Learning Innovation, Arabic